Spectacle and Spectatorship at the Nineteenth-Century American Racetrack - Natalie Zacek (European Journal of American Studies)
This paper argues that, in the antebellum United States, many people attended horse races at least as much from a desire to produce and consume spectacle as from a fascination with the sport itself. In many instances, their spectatorship was not simply directed at the actions of the horses and jockeys, but was instead focused on a broader category of spectacle, for which the nation’s preeminent racetracks became famous, and which was largely unavailable in other venues in this era, particularly outside of the new nation’s few major cities. Drawing upon a varied corpus of textual and visual sources, I contend that the greatest thrill for many race attendees was the opportunity to engage with, or at least look at, a large number of unfamiliar individuals, particularly those who occupied the highest and lowest positions in American society, especially that of the South, in which the majority of tracks were located in the pre-Civil War era. However, these audiences, unlike those who were both the subjects and the viewers of English artist William Powell Frith’s celebrated 1858 painting of Derby Day at Epsom Downs, experienced anxiety as well as entertainment from the proximity of “others,” particularly African-Americans (whether enslaved or free) and poor whites; they hoped that these groups would improve their manners by imitating those of their “betters,” but at the same time they, unlike the Epsom audiences, shied away from “crowds of the most promiscuous character.” Thus, the spectacle of human physical, social, and cultural diversity was simultaneously a source of pleasure and a harbinger of social discord.